Fabrication of pu-efb composite as a microwave substrate for patch antenna at 2.4 ghz - Syarifah Norsuhaila, Syed Mahmud (2021)
A fast progression of electronic communication on 2.4 GHz including WIFI and ISN, has resulted in a large production of electronic devices which requires a good substrate for antenna fabrication. Most of the antennas nowadays are fabricated using petroleum-based polymer resin substrate. However, the production of this kind of substrate is not environmentally friendly. The polymer resin widely used in the fabrication of electronic substrate is petroleum-based polyurethane. Agriculture waste materials are materials left in agricultural fields after the crops have been harvested. Some of it is recycled into agricultural production as fertilizer, while large amounts remain unused and, in many instances, pose a waste management problem. This waste pollutes rivers through seepage and harms the environment when it produces methane and carbon dioxide. To overcome these problems, this study was carried out to produce fully biodegradable materials for antenna fabrication. The fabrication of polyurethane-empty fruit bunch (PU-EFB) composite can be an alternative substrate for antenna fabrication. The use of palm oil as a renewable source due to the glycerol content in palm oil to produce environmental-friendly polyurethane. The formulated polyurethane in this study is using a glycerol palm oil based. The polyurethane resin was prepared by synthesis of glycerol palm oil-based and isocyanate. The PU-EFB composite was prepared with filler loading through percentage, 40%, 60% and 80% of EFB. Through the dielectric properties’ analysis on the PU-EFB composite, the value of dielectric constant of polyurethane in this study is 2.54. This value decreases when as a filler loading of EFB in PU-EFB composite increases to 2.42 for 80%, 2.33 for 60% and 2.18 for 40% EFB. The 60% filler loading of PU-EFB given the optimum value in dielectric properties. The value of dielectric constant, ε′ for 60% filler loading was 2.33. The loss factor, ε″ was 0.022 and loss tangent, tan  was 0.0093. These parameters are use in antenna design and simulation. The fabricated antenna obtained by dielectric constant, ε′ was 2.33. In the measurement of the antenna by PU-EFB substrate, the value of return loss was -38.50 dB. The resonant frequency was 2.42 GHz, and the bandwidth was 480 MHz. The PU-EFB substrate as invented by renewable source plant perchance substitutes the polymer composite that is produced by thermoset resin. The use of palm oil empty fruit bunch can upkeep the waste material management.